Vliv jaterní cirhózy na farmakokinetiku a farmakodynamiku léčiv - Perlík, F (Vnitrni lekarstvi, 2013)
Metabolic liver functions are significantly involved in the total clearance of a number of drugs. In liver cirrhosis the reduced drug elimination is a result of the blood flow through the liver, hepatocytes function and volume of hepatic tissue. Pharmacokinetic and pharmacodynamic changes depend on the nature and degree of hepatic impairment and on the characteristics of the dosed drug. Hepatocytes have a different extraction ability with respect to the individual drugs. The following are examples of drugs with high hepatic extraction: anodyne, propranolol, metoprolol, verapamil and lidocaine. These drugs are significantly dependent on the first passage through the liver. Intrahepatic and extrahepatic collateral blood flows significantly increase their bio-logical availability and reduce the clearance. The reduction in hepatic clearance of drugs with low extraction coefficient, such as chlordiazepoxide, diazepam or furosemide, is a result of its own limited functional capacity to eliminate the drug. Predicting a hepatic metabolic disorder based on a common bio-chemical assessment of enzyme activities is not sufficient. In advanced liver cirrhosis a higher risk is demonstrated for drugs with a narrow therapeutic width. It is always necessary to take into account whether the pharmacotherapy is necessary, use small doses and cautiously monitor the patient.
Keywords: antiarytmika; Liver; verapamil; játra; Analgesics; metoprolol; jaterní cirhóza; Liver Cirrhosis; propranolol; Metoprolol; Lidocaine; antihypertenziva; Antihypertensive Agents; lidokain; Hepatic Insufficiency; Anesthetics, Local; Humans; Verapamil; Risk; riziko; Propranolol; jaterní insuficience; anestetika lokální; analgetika; Anti-Arrhythmia Agents; lidé